Concurrent defects of intrinsic tellurium and extrinsic silver in an n-type Bi2Te2.88Se0.15 thermoelectric material. (June 2019) - Kim, Cham; Yang, Yeokyung; Baek, Ju Young; Lopez, David Humberto; Kim, Dong Hwan; Kim, Hoyoung
Abstract: We suggested a defect system consisting of Te- and Ag-related defects in n-type Bi2 (Te, Se)3 . We prepared the Te-rich Bi2 Te2.88 Se0.15 compound, which is expected to have Te antisite defects, via a conventional pulverization process. We devised a one-pot chemical process in which Ag nanoparticles were synthesized and instantly deposited onto the Bi2 Te2.88 Se0.15, followed by spark plasma sintering; thus, Ag atoms were inserted into the lattice structure of the Bi2 Te2.88 Se0.15 during the sintering process. Atomic layers of the Bi2 Te2.88 Se0.15 were resolved by transmission electron microscopy and dark-field scanning electron microscopy imaging with energy dispersive X-ray spectroscopy; the Ag atoms were thereby proven to occupy the interstitial sites in the Bi2 Te2.88 Se0.15 (i.e., Ag interstitial defects). The defect system composed of the Te antisites and Ag interstitials decoupled the electrical properties of the Bi2 Te2.88 Se0.15 from its thermal properties. We endeavored to adjust the defect system to maximize the decoupling effect, which resulted in the preeminent average figures of merit for operation below 150 °C ( ZT ave  = 1.22 at 25–100 °C and 1.18 at 25–150 °C) among n-type Bi2 (Te, Se)3 materials. Graphical abstract: Image 1 Highlights: We created a defect system of Te- and Ag-related defects in n-type Bi2 (Te, Se)3 . The defect system decoupled the electrical and thermal properties of a product. The decoupling effect induced excellent thermoelectric performance, as shown below. Preeminent ZT ave values (1.22 at 25–100 °C, 1.18 at 25–150 °C) were achieved.